ОСНОВНЫЕ ТЕНДЕНЦИИ И РЕГИОНАЛЬНЫЕ ОСОБЕННОСТИ ИСПОЛЬЗОВАНИЯ БАНКОВСКИХ КАРТОЧЕК (Journal of Economic Research & Business Administration, 2016)
The paper focuses on figures of bank cards market and its analysis using statistical methods: clustering method, computation of variation and sensonality indexes. The special attention is paid to the problems concerning the development of cards market in Kazakhstan regions. The results of research prove the constant growth tendencies of cards usage in Kazakhstan as well as the features of regional disproportions of wealth.